Strengthening communities' capacity through fish crackers processing technology in Konang Village, Lamongan - Abdul Aziz Jaziri; Awang Tri Satria; Rahmi Nurdiani; Jaka Suryatama (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
Community empowerment plays an important role in strengthening local economic resilience, particularly in coastal areas where fisheries are the main livelihood. In Konang Village, Lamongan, abundant aquaculture production, especially milkfish and tilapia, often faces declining prices during peak harvest seasons, leading to economic vulnerability. To address this issue, a Community Partnership Program (PKM) was implemented with the objective of enhancing the capacity of the Pertiwi Sukses Bersama community group through fish cracker processing technology. The program applied a participatory and collaborative approach, consisting of five stages: socialization, training and capacity building, technology application, mentoring and evaluation, and sustainability planning. Training modules included fish cracker production, food safety and legality (Business Identification Number/NIB, PIRT, and halal certification), as well as digital marketing using e-commerce platforms. The results showed significant improvement in participants’ knowledge and skills, reflected in post-test scores that increased from 44 to 82 on average. The group successfully acquired an NIB, initiated the process of halal and PIRT certification, and practiced digital marketing strategies. In addition, the community product was branded as “Kerupuk Ikan Bengawan” to strengthen identity and competitiveness. These achievements demonstrate that structured empowerment programs can foster sustainable fisheries-based enterprises, support the blue economy, and contribute to rural economic resilience.